Innovation performance and the role of clustering at the local enterprise level: a fuzzy-set qualitative comparative analysis approach - David Pickernell (Entrepreneurship & Regional Development, 2019)
The significance of the international, country-based conditions of entrepreneurship has been in the center of researcher’s explorations for the last few decades. Such perspective, to date, was underestimated in one of the rising streams of literature observed over the last decade: user entrepreneurship. In order to fill in this research gap, the research question of the present paper is: what is the impact of national culture, direct or not direct, on user entrepreneurship across countries? The study analyses new business units’ activities created by user innovators in the healthcare industry, exploring the effects of the four dimensions of the entrepreneurship model by Thai and Turkina. The adopted methodology uses statistical methods based on the principal component analysis (PCA), cluster analysis, and polynomial regression. The results indicate a clustering behaviour of similar scope in different countries of their occurrence. The relationship between macro level determinants and the health user entrepreneurship, is curvilinear. In particular an inverted U-shaped curve emerges, when user entrepreneurship is combined with the culture of health in a country. We detect a moderation effect of national culture on such nonlinear relationship at cross-country level.